2013
DOI: 10.1051/0004-6361/201220090
|View full text |Cite
|
Sign up to set email alerts
|

Cores, filaments, and bundles: hierarchical core formation in the L1495/B213 Taurus region

Abstract: Context. Core condensation is a critical step in the star-formation process, but it is still poorly characterized observationally. Aims. We have studied the 10 pc-long L1495/B213 complex in Taurus to investigate how dense cores have condensed out of the lower density cloud material. Methods. We observed L1495/B213 in C 18 O(1−0), N 2 H + (1−0), and SO(J N = 3 2 -2 1 ) with the 14 m FCRAO telescope, and complemented the data with dust continuum observations using APEX (870 µm) and IRAM 30 m (1200 µm). Results. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

92
652
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 391 publications
(748 citation statements)
references
References 69 publications
92
652
4
Order By: Relevance
“…If we take 0.1 pc as the mean filamentary width, then the estimated line masses of filamentary structure in the immediate vicinities of prestellar cores throughout L1495 are in the range 32 ± 15 M⊙ pc −1 . Our mean value is about a factor of two larger than the value 15 M⊙ pc −1 found by Hacar et al (2013) using N2H + observations, and the value 17 M⊙ pc −1 found by Schmalzl et al (2010) based on near-infrared extinction measurements. The reason for the discrepancy is not clear, but it is significant that all three estimates are greater than or equal to the theoretical value of 16 M⊙ pc −1 for an isothermal cylinder in pressure equilibrium at 10 K (Inutsuka & Miyama 1997).…”
Section: Relationship To Filamentscontrasting
confidence: 71%
See 1 more Smart Citation
“…If we take 0.1 pc as the mean filamentary width, then the estimated line masses of filamentary structure in the immediate vicinities of prestellar cores throughout L1495 are in the range 32 ± 15 M⊙ pc −1 . Our mean value is about a factor of two larger than the value 15 M⊙ pc −1 found by Hacar et al (2013) using N2H + observations, and the value 17 M⊙ pc −1 found by Schmalzl et al (2010) based on near-infrared extinction measurements. The reason for the discrepancy is not clear, but it is significant that all three estimates are greater than or equal to the theoretical value of 16 M⊙ pc −1 for an isothermal cylinder in pressure equilibrium at 10 K (Inutsuka & Miyama 1997).…”
Section: Relationship To Filamentscontrasting
confidence: 71%
“…The spatial filtering does, however, serve to show the smaller scale features superposed on the overall filament structure. Some of these features are in the form of threadlike structures which correspond very well to the velocity coherent "fibres" identified by Hacar et al (2013) in C 18 O (see Fig. 2 of André et al 2014).…”
Section: Relationship To Filamentssupporting
confidence: 69%
“…Indeed, star-forming cores in nearby spiral-arm clouds are often located along dense filaments (Polychroni et al 2013;Könyves et al 2015) and young star clusters tend to form at their intersections (Myers 2011;Schneider et al 2012). Recent observations and simulations of spiral-arm clouds show that filaments have coherent velocities (Hacar et al 2013Moeckel & Burkert 2015;Smith et al 2016) and orientations preferentially (but not always) perpendicular to the magnetic field (Gaensler et al 2011;Sugitani et al 2011;Hennebelle 2013;Palmeirim et al 2013;Planck Collaboration et al 2016a, 2016b, 2016cTomisaka 2014;Zhang et al 2014;Pillai et al 2015;Seifried & Walch 2015). Most importantly, filaments seem to have a nearly universal widthW 0.1 pc fil (Arzoumanian et al 2011;Juvela et al 2012;Malinen et al 2012;Palmeirim et al 2013;Benedettini et al 2015;Kirk et al 2015;Roy et al 2015;Salji et al 2015;Wang et al 2015;Kainulainen et al 2016).…”
Section: Universal Filament Properties?mentioning
confidence: 99%
“…Models and methods As the initial condition, a filamentary molecular cloud is considered because recent observations have shown that molecular clouds often exhibit filamentary structures [10,11,12]. The filament is assumed to be infinitely long and in an equilibrium state where thermal pressure supports an isothermal cloud against its self-gravity.…”
mentioning
confidence: 99%